2009
DOI: 10.3758/mc.37.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment in the weapon focus effect

Abstract: Two experiments are reported in which postevent source of misinformation was manipulated within weaponpresent and weapon-absent scenarios. Participants viewed slides depicting either a weapon or a newspaper event and then received either incomplete questioning or a narrative. Both postevent sources contained misleading information about a central and peripheral detail concerning either the weapon or the newspaper scenario. With a modified test in Experiment 1, questioning was found to increase misinformation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…A second finding that is consistent with the inhibitory account is that retrieval-induced forgetting is dependent on the strength of the competitor (Anderson et al, 1994;Saunders, 2009). Specifically, retrieval-induced forgetting occurs only when the competing items are strong (as measured by taxonomic strength).…”
Section: Experiments 1 Does Mental Imagery Evoke Retrieval-induced Forsupporting
confidence: 68%
“…A second finding that is consistent with the inhibitory account is that retrieval-induced forgetting is dependent on the strength of the competitor (Anderson et al, 1994;Saunders, 2009). Specifically, retrieval-induced forgetting occurs only when the competing items are strong (as measured by taxonomic strength).…”
Section: Experiments 1 Does Mental Imagery Evoke Retrieval-induced Forsupporting
confidence: 68%
“…For example, Zaragoza and Lane (1994) found that presenting misinformation in questions increased suggestibility relative to presenting misinformation in a narrative. Similarly, Saunders (2009) reported that misleading questions are more effective at inducing false memories than is a narrative, though this effect was only observed for misinformation regarding central details and not peripheral details. Gobbo (2000) showed that presenting misinformation in questions alone produced a smaller misinformation effect than presenting misinformation in both questions and a narrative (such that the misinformation was repeated).…”
Section: Testing Increases Suggestibility For Narrative-based Misinfomentioning
confidence: 99%
“…Some researchers have defined central and peripheral information as details that are important and incidental to the thrust of the witnessed event, respectively (Dalton & Daneman, 2006;Loftus 1979;Wright & Stroud, 1998). Others defined centrality based on the frequency that those details are reported in free recall, with more frequently recalled items classified as central and less frequently recalled items as peripheral (Heath & Erickson, 1998;Saunders, 2009). We opted to define item centrality in the latter way because this definition is quantifiable and arguably more objective.…”
Section: Applied Implications Of Retrieval-enhanced Suggestibilitymentioning
confidence: 99%